Does political inclusion of rebel parties promote peace after civil conflict?. Issue 6 (18th September 2016) - Marshall, Michael Christopher; Ishiyama, John
ABSTRACT: Does the inclusion of rebel parties into the post-conflict political process help contribute to peace after the end of conflict? In this article we examine whether the transformation of rebel groups into political parties actually leads to the development of a durable peace after a civil war. Examining the likelihood of recurrence of civil wars in a country and recurrence of conflict in government–rebel group dyads after a settlement, we find that the inclusion and participation of former rebel parties in national government has an important impact on the likelihood of a durable post-settlement peace. Most importantly, not excluding major rebel parties from access to governing institutions is the most important factor in promoting post-conflict peace.